A bibliometric analysis of the water-energy-food nexus based on the SCIE and SSCI database of the Web of Science - Fan, Jing-Li; Wang, Qian; Zhang, Xian (Mitigation and adaptation strategies for global change, 2021)
In the context of climate change mitigation and adaptation, the concept of the water-energy-food nexus (WEF nexus) has resulted in an increased focus on the long-neglected potential trade-offs between the water, energy, and food sector. In this study, we obtained 3077 publications from the Science Citation Index Expanded (SCIE) and the Social Sciences Citation Index (SSCI) in the Web of Science. A bibliometric method was used to characterize the publications, the participating countries, and the research trends in the field of the WEF nexus. The results show (i) the number of scientific publications increased exponentially from 2011 to June 2019, with an average annual growth rate of 27.87%. (ii) The Journal of Geophysical Research: Atmospheres had the most publications related to WEF nexus research. (iii) Environmental Sciences Ecology was the subject category with the most publications. (iv) WEF nexus research was led by the USA, which produced 40.14% of the publications in this field, and five of the ten most influential institutions are American institutions. (v) China ranked in second place regarding publication volume and exceeded the UK in 2016 in annual publications. The Chinese Academy of Sciences was the most productive research institution. (vi) Academic collaboration between countries was widespread in the WEF nexus field; the top 10 most productive countries all had high proportions of collaborative publications (> 40%), and Austria had the highest percentage (91.49%). (vi) Co-word analysis indicated that the term map had three clusters in 1988–2011 focusing on biological production, climate and meteorology, and land surface research. In 2012–2019, the term map also had three clusters, including experimental research on recyclables, resource management, and land-atmosphere interactions. Frequency analysis of the keywords in different countries showed different research emphases in the top 10 most productive countries. The analyses of frequently used keywords also revealed the research hotspots and trends. “Climate change” was the second most frequently used keyword in these countries. The interpretation of climate change mitigation and adoption strategies from the WEF nexus perspective is an important research direction.